Meningkatkan Keterampilan 4c dengan Literasi Digital di SMP Negeri 1 Sidoharjo - Budi Sriyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
This school action research aims to improve the 4C skills (critical thinking, creativity, communication, creativity and innovation, collaboration) of teachers with digital literacy application activities at SMP Negeri 1 Sidoharjo. The research setting was the subject teacher at SMP Negeri 1 Sidoharjo in the 2020/2021 school year. As research subjects are teachers, the principal at the junior high school is a researcher and assisted by an observer. This study consisted of 2 cycles. During the application of digital literacy activities, observations were made of teacher performance through observation, sociometry, and questionnaire sheets. Other findings during the course of the action were discussed between the researcher and the observer, equipped with data from the observations that were carried out by reflection in each cycle. The results of the study in cycle 1 and cycle 2 showed an increase in the 4C skills of teachers. The results of observations, sociometry, and questionnaires on the 4C skills of the teacher showed that in cycle 1 the average critical thinking score was 76%, creativity 76%, communication 75%, creativity and innovation 76%, 76% collaboration on good criteria and in cycle 2 average critical thinking score 87%, creativity 85%, communication 86%, creativity, and innovation, collaboration 84% on very good criteria.